Are We Listening? Obstetric Anesthesiology and the National Call for Birth Justice and Accountability: A Perspective From the United States. Issue 1 (March 2022) - Ejiogu, N.I.
Abstract : ( Int J Obstet Anesth. 2021;46:102978) Black and Indigenous people in the United States are disproportionately affected by severe complications in pregnancy and childbirth. Compared with white parturients, Black parturients are 3 times more likely to die from pregnancy-related causes. This disparity takes place in the context of the COVID-19 pandemic and increased awareness of police violence, both of which disproportionately affect Black, Brown, Indigenous, poor, and disabled communities. This short report uses the author's personal experiences to recommend steps the medical community can take to actively address birth justice.